TO WHAT EXTENT THE USE OF COMMUNICATIVE APPROACH IN THE TEACHING OF ENGLISH AS A FOREIGN LANGUAGE BY TEACHERS OF SENIOR HIGH SCHOOLS IN BENGKALIS - A. Malik; M.I Gunawan (Politeknik Negeri Bengkalis, 2018)
This study aimed tofind out to what extent the use of communicative approach in the teaching of english as a foreign language by teachers of senior high schools in Bengkalis. This study was done to see the phenomenon of lack of communication skill in English at the number of senior high school graduation. It might be caused of inappropriate approach applied at senior high school. This study found that most teachers strongly agreed that their role is as a facilitator. Furthermore, most teachers indicated that their class is more student centered than teacher- centered, the teacher is just as a facilitator in the classroom. This study could be used as empirical data for further research and as a review for the stockholders in making decision. Finally, this study could contribute to improve the senior high school graduation ability in English.